PENERAPAN MANAJEMEN E-COMMERCE UNTUK MENINGKATKAN INOVASI PRODUK KERAJINAN KELOMPOK GERAI KEMBANG SETAMAN TIRTA SIAK KECAMATAN PAYUNG SEKAKI KOTA PEKANBARU - Sukri Sukri; Susi Endrini; Salamun Salamun; Wahyu Ramdhan; Kenepri Kenepri (Jurnal Hilirisasi IPTEKS, 2024)
The purpose of the service activity is to investigate efforts to revive the local trade sector through product innovation by the Kembang Setaman outlet group, which is implemented through the use of e-commerce management to increase turnover in the Tirta Siak Village area, Payung Sekaki District, Pekanbaru City. Technological developments and shifts in consumer behavior towards digital platforms have provided new opportunities for small and medium scale businesses to expand their reach and optimize their product marketing. The method of the activity is a qualitative approach with a case study, through in-depth interviews with members of the Kembang Setaman outlet group and analysis of the implementation of e-commerce management in their marketing strategy. The results of the activity show that the use of e-commerce has had a positive impact on increasing the turnover of the outlet group. Various product innovations were made, such as improving product quality, product diversification, and a more flexible pricing strategy. However, the service also identified several challenges, including limited access to technology, limited understanding of e-commerce operations, and increasing competition in the digital environment. Therefore, support from the local government, training on technology utilization, and an integrated marketing strategy are key in maintaining the sustainability and success of local trade businesses.